Trends in Prosthodontics - A Review - Pratheebha C1 , Keerthi Sasanka2 , Gifrina Jayaraj3 , Visalakshi Ramanadhan4 , Dhanraj Ganapathy5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Prosthodontics is concerned with the impact of tooth or tissue damage and partial or complete loss of teethon oral function in its broadest sense. It deals with this largely through prosthetic replacement. The disciplineoccupies a major portion of a dental school curriculum, and dental practitioners usually devote much of theirpractice to prosthodontic services. It is continuously evolving consequent to the rapid advancements in dentalbiomaterials science, clinical and laboratory techniques and technologies, education, research, therapeutics,literature, and interdisciplinary developments. While the basic process of making dentures has changed littleover the past several decades, new materials and techniques can help laboratories and clinicians providefunctional, esthetic restorations that offer exceptional value to patients. Implant treatment is a tremendousadjunct to removable prosthodontics in the treatment of edentulous patients, but it is not within the financialreach of all dental patients.In future, prosthodontics has a very good scope and it is going to be beneficial forthe patients who are edentulous.Technology developments are very much needed in future for its very wellestablishments .This review is aimed to discover some fascinating facts about the trends that are prevailingin prosthodontics and its future scope.